Penggunaan Gadget dan Literasi Media: Menyiapkan Siswa SDK Lewopnutung untuk Era Digital yang Aman dan Bertanggung Jawab - Aso, Rosalinda; P. Lamawitak, Yohana Imeldahlia; Riang, P. Yoseph (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
The use of social media among elementary school children is increasing along with the development of information and communication technology. However, unwise use of social media can cause various problems, such as the spread of hoaxes, cyberbullying and negative content. This research aims to empower SDK Lewopenutung elementary school children through social media literacy, with a focus on socializing Gadget Use and Media Literacy: Preparing SDK Lewopenutung Students for a Safe and Responsible Digital Era. The methods used include training, workshops, practice, as well as mentoring and periodic evaluations. The training includes material on safe use of social media, creating positive content, and internet ethics. The results of this program show increased student awareness of the importance of ethics in using social media, increased technical skills in managing social media, and more positive behavioral changes. The evaluation shows that this program is very relevant to students' needs in the digital era and has the potential for further development. Despite challenges such as limited access to the internet, continued support from various parties can ensure the long-term success of this program long.